Evaluasi Pascapelatihan pada Kelompok Tani Hutan Pemegang Izin Perhutanan Sosial di Jawa Barat dan Jawa Tengah Tahun 2019 - Amin Fauzi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Social forestry is sustainable forest management system implemented by local communities of Forest Farmer Group (FFG) aiming to increase community welfare, environmental balance and social cultural dynamics. Environment and Forestry Training Center Kadipaten conducted training to support social forestry programs with on-site model and was held August‒October 2018 in West Java and Central Java. The post-training evaluation was conducted one year after the training finished from June‒August 2019. The post-training evaluation aims to assess the suitability of the training materials with the needs of the farming business and the benefits of the training on the farming business developed by KTH. Data collection is done through questionnaires and interviews. The data analysis used descriptive analysis. The evaluation results on several training, i.e measurement and participatory mapping of social forestry areas, agroforestry engineering, oyster mushroom cultivation, making, packaging and marketing of bokashi, and nature tour guide showed that aspects of the relevance of the training to the needs of farming businesses are in the medium to high categories. The benefits of training to the farming businesses are in the medium and high category. To improve the quality of the training process and results, it is necessary to conduct a more careful analysis of training needs so that the training program is in line with the needs of the target community.